2007
DOI: 10.1063/1.2778358
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally narrowed edge emission from organic light-emitting diodes

Abstract: A dramatic spectrally narrowed edge emission (SNEE) from small molecular organic light-emitting diodes at room temperature, with a full width at half maximum of 5–10nm, is described. The results show that this emission is due to irregular waveguide modes that leak from the indium tin oxide anode to the glass substrate at a grazing angle. Measurements of variable stripe length devices exhibit an apparent weak optical gain, but there is no observable threshold bias associated with this SNEE. Hence this apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Other claims of electrically-driven stimulated emission have been reported during the XXI th century: Yokoyama et al [126] observed a spectral narrowing of the edge emission of an OLED as well as an intriguing superlinear dependence of the emission with the electrode length, which was attributed to the presence of stimulated emission. Tian et al [24] observed the same features but suggested that a misalignment of the collecting optics could be the reason for the observed superlinear dependence instead of gain. In both cases, the spectral narrowing can be well accounted by a resonant leaky mode at the cut-off frequency [126].…”
Section: Prospects For Electrical Pumpingmentioning
confidence: 70%
See 1 more Smart Citation
“…Other claims of electrically-driven stimulated emission have been reported during the XXI th century: Yokoyama et al [126] observed a spectral narrowing of the edge emission of an OLED as well as an intriguing superlinear dependence of the emission with the electrode length, which was attributed to the presence of stimulated emission. Tian et al [24] observed the same features but suggested that a misalignment of the collecting optics could be the reason for the observed superlinear dependence instead of gain. In both cases, the spectral narrowing can be well accounted by a resonant leaky mode at the cut-off frequency [126].…”
Section: Prospects For Electrical Pumpingmentioning
confidence: 70%
“…First of all, the quest of the "organic laser diode" remains the top keyword that drives the scientific community. Many insights contributed to a better understanding of the bottlenecks caused by the supplementary losses brought by electrical excitation; surprisingly though, some claims of apparent gain or lasing action [23] under electrical excitation have been published, but they were later attributed to artefacts [24] or mistaken identification of laser action [25]. These aspects will be reviewed in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…Such measurements are typically conducted to provide evidence for optical gain, and consequent ASE in inorganic semiconductors and optically pumped organic films. 9,10 To our knowledge, our preceding paper 8 and this paper describe the first detailed VSL measurements in electrically pumped organic devices. When conducting the VSL measurements, the length of the Al cathode was shortened for each step, by either 1 or 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…This paper describes striking spectrally narrowed edge emission ͑SNEE͒ from small molecular OLEDs ͑SMOLEDs͒ 7,8 and measurements on these devices with variable stripe length ͑VSL͒, 9,10 which exhibit an apparent weak optical gain. These are two key features of amplified spontaneous emission ͑ASE͒, i.e., mirrorless lasing.…”
Section: Spectrally Narrowed Edge Emission From Leaky Waveguide Modesmentioning
confidence: 99%
“…We therefore attribute this to the existence of leaky waves with propagation angles close to the critical angle for TIR and travelling in a direction nearly parallel to the layer interface. [14,15] The fluorescence inside the film effectively couples to these leaky modes leading to the much wider edge emission.…”
mentioning
confidence: 99%